How Will China's Saving-Investment Balance Evolve? - Kuijs, Louis (World Bank, Washington, DC, 2012)
This paper investigates how China's saving, investment, and saving-investment balance will evolve in the decades ahead. Household saving in China is relatively high compared with OECD countries. However, much of China's high economywide saving, and the difference between China and other countries, are due to unusually high enterprise and government saving. Moreover, cross-country empirical analysis shows that economywide saving and investment in China are higher than what would be expected, even adjusting for differences in economic structure. Combined, these findings suggest that much of China's high saving is the result of policies particular to China. Looking ahead, the econometric results suggest that purely on the basis of projected structural developments-including development, changes in economic structure, urbanization, and demographics-saving and investment would both decline only mildly in the coming two decades, with ambiguous impact on the current account surplus. However, the potential effect on saving, investment, and the saving-investment balance of several policy adjustments could be large. Several of these policies are identified and their likely impact assessed and quantified. This exercise suggests that rebalancing along these lines should reduce both saving and the current account surplus over time, although the surplus is unlikely to turn into a deficit soon.